Optimalisasi Sosialisasi dan Pelayanan Administrasi Perkawinan sebagai Upaya Meningkatkan Kesadaran Hukum Masyarakat di Kantor Urusan Agama Kecamatan Turikale Kabupaten Maros: Optimization of Socialization and Marriage Administration Services as an Effort to Increase Public Legal Awareness at the Religious Affairs Office, Turikale District, Maros Regency - Setiawan, Isal; Indri Karadona, Rosika (Anotero Lembaga Scientific Pekanbaru, 2025)
Marriage is a social institution that plays an important role in people's lives. In Indonesia, official marriage registration is an obligation in accordance with Law Number 1 of 1974 concerning Marriage. However, many people still do not understand the importance of marriage registration, which has the potential to cause various legal problems. This community service activity aims to optimize the socialization and administration of marriage services in order to increase public legal awareness, especially in Turikale District, Maros Regency. The method used in this activity is Participatory Action Research (PAR) which involves various stakeholders, including KUA officers, community leaders, and prospective brides and grooms. The main activities carried out include marriage guidance (Suscatin) for prospective brides and grooms and socialization of marriage law. The results of this program show an increase in public understanding of marriage administration procedures, rights and obligations in marriage, and the legal consequences of unregistered marriages. The positive impacts of this activity include an increase in the number of couples who officially register their marriages, an increase in public legal awareness, and an improvement in the quality of administrative services at the KUA. For the sustainability of the program, it is recommended that the KUA Turikale District continue to improve marriage administration information services through various media, strengthen synergy with community leaders, and consider implementing a digital-based administration service system to facilitate public access to marriage registration.